The association between gut microbiome and hypertension varies according to enterotypes: a Korean study - Song, Ju Sun; Kim, Joung Ouk Ryan; Yoon, Sung Min; Kwon, Min-Jung; Ki, Chang-Seok (Frontiers in Microbiomes, 2023)
Several animal and clinical studies have reported that the state of the human gut microbiome is associated with hypertension. In this study, we investigated the association between the gut microbiome and hypertension in a Korean population from an enterotypic perspective. A total of 623 participants were enrolled from a healthcare center and classified into four enterotypes, Bacteroides1- (Bac1), Bacteroides2- (Bac2), Prevotella- (Pre), and Ruminococcus enterotype-like-composition (Rum). When comparing the four enterotypes, clinical characteristics related to obesity, metabolic syndrome, and blood pressure were significantly associated with the enterotypes, showing unfavorable associations with the Bac2 group and the opposite for the Rum group. Similarly, the prevalence of hypertension was highest in the Bac2 group and lowest in the Rum group. When analyzing the association between gut microbiota and blood pressure for each enterotype, gut microbial features of lower diversity, depletion of important short chain fatty acid-producing taxa, such as Faecalibacterium, Blautia, Anaerostipes, and enrichment of lipopolysaccharide -producing taxa, such as Megamonas, were found only in the dysbiotic Bac2 group. From an enterotype perspective, this study on a large Korean cohort shows that low-diversity Bacteroides2-enterotype-like composition is associated with hypertension, while the reverse is true for high-diversity Ruminococcus-enterotype-like composition and, to a limited degree, Bacteroides1-enterotype-like composition. In addition, we suggest that the effect of gut microbiota-mediated risk of hypertension could be modulated by altering the gut microbiome via diet. Dietary intervention trials promoting a balanced Korean diet instead of a more Western alternative may provide more definitive evidence for the involvement and role of the gut microbiome in relation to blood pressure.